2007
DOI: 10.1007/s11626-007-9064-y
|View full text |Cite
|
Sign up to set email alerts
|

Adult rat bone marrow stromal cells differentiate into Schwann cell-like cells in vitro

Abstract: Bone marrow stromal cells (MSCs) have the capability of differentiating into mesenchymal and non-mesenchymal lineages. In this study, MSCs isolated from adult Sprague-Dawley rats were cultured to proliferation, followed by in vitro induction under specific conditions. The results demonstrated that MSCs were transdifferentiated into cells with the Schwann cell (SC) phenotypes according to their morphology and immunoreactivities to SC surface markers including S-100, glial fibrillary acidic protein (GFAP) and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 39 publications
(38 reference statements)
1
27
0
1
Order By: Relevance
“…Chitosan is shown to be a favorable conduit to fill with differentiated Schwann cells for transplantation [74]. Histologically, transplanted cells were confirmed to form myelin and express myelin-related proteins such as MAG, myelinbasic protein, P0 or peripheral myelin protein 22 (PMP22) [22,65,75,76].…”
Section: • Bmscsmentioning
confidence: 99%
“…Chitosan is shown to be a favorable conduit to fill with differentiated Schwann cells for transplantation [74]. Histologically, transplanted cells were confirmed to form myelin and express myelin-related proteins such as MAG, myelinbasic protein, P0 or peripheral myelin protein 22 (PMP22) [22,65,75,76].…”
Section: • Bmscsmentioning
confidence: 99%
“…This induction system resulted in a rate of 42.9 ± 3.3% S100-positive cells. Lin et al [19] reported pre-induction using b-mercaptoethanol, and then supplementing with some related factors could result in a rate of 25% S100-positive cells. We adopted a two-step induction protocol of the HUMSCs: at first, the long spindle-shaped HUMSCs were induced into neural stem cell like structures (neurospheres), and then some factors were added into the culture medium to further induce the neurospheres to differentiate into neuron-like cells bearing morphological, immunophenotypic and functional resemblances with Schwann-like cells, which avoid the harmfulness of b-mercaptoethanol to the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…These stem cells can be induced to differentiate into SClike cells by using platelet-derived growth factor, basic fibroblast growth factor, and glial growth factor-2 (Keilhoff and Fansa 2011). Studies have demonstrated that more than 50 % of cells differentiated with this protocol (Dezawa et al 2001) typically exhibit SC-like phenotypes and, more importantly, that they successfully support nerve regeneration (Caddick et al 2006;Keilhoff et al 2006a, b;Lin et al 2008). Specifically, differentiated BMSCs exert a significant neurotrophic effect via secretion of factors that support neuronal survival and growth affecting both outgrowing fibers and nerve cell bodies in a dorsal root ganglion neuronal functional assay (Caddick et al 2006;Mahay et al 2008).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%